The essentials physics of medical imaging - Bushberg, Jerrold T. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"The basic science important to nuclear imaging, including the nature and production of radioactivity, internal dosimeters and radiation detection and measurement, are presented clearly and concisely. Current concepts in the fields of radiation biology and radiation protection relevant to medical imaging, and a number of helpful appendices complete this comprehensive textbook. The text is enhanced by numerous full color charts, tables, images and superb illustrations that reinforce central concepts. The book is ideal for medical imaging professionals, and teachers and students in medical physics and biomedical engineering. Radiology residents will find this text especially useful in bolstering their understanding of imaging physics and related topics prior to board exams."